Expression of Nuclear Factor Kappa B and Survivin in Psoriasis. (25th November 2012) - Gunduz, Kamer; Temiz, Peyker; Gencoglan, Gulsum; Inanir, Isil; Catalkaya, Arzu
Abstract : Background and Objective . Suppression of apoptosis has been proposed as a mechanism responsible for epidermal thickness in psoriasis. Survivin is a member of the inhibitor of apoptosis family. Nuclear factor kappa B (NF- κ B) is one of the transcriptional factors that regulate many genes affecting apoptosis. The aim of this study was to determine survivin and NF- κ B expressions in psoriasis in comparison with normal epidermis. Patients and Methods . Immunohistochemical expressions of survivin and NF- κ B were investigated in 41 psoriatic and 21 normal skin samples. Results . Diffuse nuclear survivin expression in all epidermal layers was seen in all of the psoriatic samples. NF- κ B expression in different epidermal locations was seen in all of the psoriatic samples. Nuclear staining was positive in 40 psoriasis samples. Similar survivin and NF- κ B expressions were observed in normal skin samples. Conclusion . Since similar expressions are seen in both normal and psoriatic epidermis, no important roles for survivin and NF- κ B can be attributed in epidermal proliferation and thickness seen in psoriasis.